ANALISIS PENDAPATAN DRIVER GOJEK PADA MASA NEW NORMAL DI KOTA DENPASAR - Indrayani, Ni Wayan Eka; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 11 (2024): Vol.13.No.11. NOVEMBER 2024 [765-830]DO - 10.24843/EEP.2024.v13.i11.p04, 2025)
The paradigm of human mobility has evolved as a result of the emergence of transportation tools, especially online transportation services such as Gojek. The purpose of this study is to examine the effect of distance, working hours, age, dan volume of service transactions on the income of Gojek drivers in Denpasar City during the New Normal period. Data was collected using quantitative techniques dan associative design by surveying active Gojek drivers in Denpasar City. The analysis findings show that these parameters have an impact on Gojek drivers' income simultaneously, with mileage dan working hours having a positive dan substantial impact, while age has a negative impact dan the number of service transactions has a beneficial impact. Younger drivers often make more money, dan the quantity of service interactions is a factor in income growth. The results of this study provide a more thorough knowledge of the variabels that affect Gojek drivers' income, which can guide drivers dan online transportation service businesses in maximizing income potential. This study also provides insight into the impact of the New Normal Era dan the COVID-19 pdanemic on online transportation services dan driver income.   keyword : income, Gojek driver, new normal-era Klasifikasi JEL: R480, R410, I180